Keynote Address:: The Rolling Head’s “Grave” yard - Skydancer, Louise (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
No one knows the origins of the ancient story “The Rolling Head.” It has been told in many ways by many bands and in many families. An effort to unravel the story’s philosophy, psychology and spirituality through an exploration of its major symbols leads to more questions than answers. For Halfe, examining the emotional immediacy of Cihicipistikwan, the Rolling Head, the Elders, and boys, and other symbolic elements in the tale reveals its cultural richness but the story ultimately defies explanation. David Suzuki’s The Sacred Balance: Rediscovering Our Place in Nature offers useful insights when considering this ageless and complex narrative.